(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Introduction. In recent years, symptoms such as anemia, fever, and general weakness have become more common, and these symptoms are often not considered the onset of serious illnesses. However, they can be clinical manifestations of serious infectious diseases. One such disease is visceral leishmaniasis, which can present with symptoms such as fever, chills, anemia, or bicytopenia with hepatosplenomegaly.